ISTEC Library Linkage Initiative - De Giusti, Marisa Raquel (2023)
The following presentation outlines the activities of the Ibero-American Consortium for Education in Science and Technology and its Library Linkage initiative. It elaborates on the development of the Celsius software up to its 3.0 version and discusses the evolution of bibliographic exchange among the affiliated libraries over the past two decades.